Asset Overhang and Technological Change - Degryse, Hans; Roukny, Tarik; Tielens, Joris (Review of Financial Studies, 2026)
Abstract Investors face reduced incentives to finance technological change that devalues their legacy investments. We formalize this “asset overhang” and apply our framework to the climate-banking nexus. Leveraging (1) firm-level data on green innovation and diffusion and (2) the sets of product and technology market peers, we implement a shift-share design that identifies banks’ credit facilities impacted by green firm activities. We find that green firms imposing an asset overhang across all lenders are 3 to 7 percentage points more likely to report tight credit supply conditions. The presence of legacy-free investors mitigates the asset overhang problem, thereby facilitating technological change.